非小细胞肺癌神经内分泌分化与其生物学特性及预后关系的研究 (Zhongguo Fei Ai Za Zhi, 2010)
BACKGROUND AND OBJECTIVE: Recently it has been proven that non-small cell lung cancer (NSCLC) also had the feature of neuroendocrine (NE) differentiation. The aim of this study is to investigate the correlation between NE differentiation of NSCLC and its biological behaviors, together with prognosis. METHODS: All NSCLC paraffin-embedded specimens and cases, followed up over than 3 years, were randomly obtained from 206 patients from January 2005 to December 2007, who underwent surgical resection and confirmed pathologically. All of them were not underwent radiation and chemotherapy before operation. Immunohistochemical Envision two-step method was used to detect the expressions of NSE, CgA and Syn. And all data were analyzed using SPSS statistics software and Kaplan-Meier survival curves were constructed, and Log-rank test was also conducted. RESULTS: Of the 206 patients, 84 cases with NE differentiation (39.8%) and CgA, NSE and Syn positive rates were 53 (25.7%), 104 (50.5%), 91 (44.2%) respectively; a statistically significant difference between NSCLC with NE differentitation were showed. The positive expression of Syn was closely correlated with histological differentiation, lymph node metastasis. The survival of single-factor analysis by the Log-rank test showed that Syn had relation to the postoperative survival rate of patients (χ(2)=4.164, P=0.041), while the relevance between patients with NE and survival had no significant difference (P > 0.05). CONCLUSION: NE differentiation is an important indicator of biological behavior of NSCLC; and the detection of Syn markers of neuroendocrine differentiation may be recommended to detect NE differentiation of NSCLC, and the positive expression of Syn suggests poor prognosis.